Aspects of the masculine - Jung, C. G. (Carl Gustav), 1875-1961 (Bollingen series., 1989)
A collection from the Bollingen series of Jung's most important contributions to the psychological understanding of masculinity, not only the psychology of men but also the essence of masculinity in both sexes. Translated by R.F.C. Hull; edited and with an introduction by John Beebe, a psychoanalyst who practices in San Francisco. No index. Annotation copyrighted by Book News, Inc., Portland, OR.